2018
DOI: 10.1128/jvi.01117-18
|View full text |Cite
|
Sign up to set email alerts
|

T5 Exonuclease Hydrolysis of Hepatitis B Virus Replicative Intermediates Allows Reliable Quantification and Fast Drug Efficacy Testing of Covalently Closed Circular DNA by PCR

Abstract: Chronic infection with the human hepatitis B virus (HBV) is a major health problem. Virus persistence requires the establishment and maintenance of covalently closed circular DNA (cccDNA), the episomal virus template in the nucleus of infected hepatocytes. Compared to replicative DNA intermediates (relaxed circular DNA [rcDNA]), copy numbers of cccDNA in infected hepatocytes are low. Accordingly, accurate analyses of cccDNA require enrichment of nuclear fractions and Southern blotting or selective quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 58 publications
3
61
0
2
Order By: Relevance
“…Total cellular DNA was extracted from Huh7-NTCP cells after infection with 200 mge of WT or ΔHBc HBV and analysed by inverse nested PCR at 7dpi ( Figure S4). We found that WT and ΔHBc HBV integrated at a geometric mean frequency (± geometric SD factor) of 4.82 x 10 -5 (±2.36) and 5.97 x [6,36,38]. Our finding also confirms previous work that demonstrated that a more than genome length construct carrying a HBc stop mutation can be rescued by trans-complementation with a HBc expressing plasmid [39] to produce replication-deficient virions.…”
Section: Hbv Dna Integration Does Not Depend On Hbc Expressionsupporting
confidence: 89%
See 1 more Smart Citation
“…Total cellular DNA was extracted from Huh7-NTCP cells after infection with 200 mge of WT or ΔHBc HBV and analysed by inverse nested PCR at 7dpi ( Figure S4). We found that WT and ΔHBc HBV integrated at a geometric mean frequency (± geometric SD factor) of 4.82 x 10 -5 (±2.36) and 5.97 x [6,36,38]. Our finding also confirms previous work that demonstrated that a more than genome length construct carrying a HBc stop mutation can be rescued by trans-complementation with a HBc expressing plasmid [39] to produce replication-deficient virions.…”
Section: Hbv Dna Integration Does Not Depend On Hbc Expressionsupporting
confidence: 89%
“…Wild-type and ΔHBc HBV establish comparable levels of cccDNA in HBV-susceptible cells and then analysed intracellular cccDNA levels at 7 and 14dpi by Southern blot (Figure 3A). As shown previously [36], cccDNA was detectable at 7 and 14dpi with WT virus without a significant increase within the second week. Formation of cccDNA could be blocked by MyrB, confirming receptor mediated entry as a prerequisite for cccDNA formation.…”
Section: Production and Characterisation Of Hbc-deficient (δHbc) Hbvsupporting
confidence: 86%
“…Quantitative analysis of HBV DNA and HBV RNA was performed using Hepatitis B Viral DNA/RNA Quantitative Fluorescence Diagnostic Kit (ShenXiang, China) according to the manufacturer's protocol. Hirt extraction and T5 exonuclease digestion for cccDNA PCR quantification . Cytotoxicity was assessed by CCK‐8 (Bimake) and flow cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel to this, compound 1 (567 mg, 3.5 mmol) was suspended in dry toluene (20 mL), and three drops DMF and oxalyl chloride (1.0 mL, 11.8 mmol) were added at RT, then warmed to 50°C and stirred for to afford the desired product as shown in supplement (S1). 14,15 Cytotoxicity was assessed by CCK-8…”
Section: Hatumentioning
confidence: 99%
“…International HBV meeting (62). Levels of cccDNA were measured by quantitative real-time PCR (qPCR) using the TaqMan Gene Expression Master Mix (Applied Biosystems), specific primers, and probe as described previously (63). Data were processed as 2 (−ΔΔCt) for quantification of cccDNA using GAPDH (via primer-probe set Hs04420697_g1; Applied Biosystems) as an internal normalization control.…”
Section: Dna Extraction and Cccdna Quantificationmentioning
confidence: 99%